Changes in employment technology under the influnence of the new technologies - Vasković Vojkan (Trendovi u Poslovanju)
Establishing communication between job candidates and companies has always been a priority for both sides. The Internet and Internet technologies brought significant changes in communication methods and expanded opportunities for both parties. From the company's point of view finding the adequate candidates is a demanding task. It needs to broadcast vacancies publicly and make them visible to a large number of potential employees. Based on the received job applications, it is necessary to select the right applicants. New technologies allow pre-selection without the need of candidates physical presence, which significantly reduces costs. From the aspect of job candidates, changes in communication have brought significant advantages. Exploring for a potential jobs is easier via the Internet, applying and sending application documents is simplified and with minimal costs. The opportunity for the candidates to present their skills, creates good preconditions for the employment. The paper analyzes the possibilities for the selection of employees by companies and the potential that the Internet provides to individuals to find vacancies and apply for jobs. Special attention has been put on the analysis of the job databases as well as databases of those who are willing to offer their knowledge and find an employment.